1999
DOI: 10.1109/36.803418
|View full text |Cite
|
Sign up to set email alerts
|

Models and methods for automated material identification in hyperspectral imagery acquired under unknown illumination and atmospheric conditions

Abstract: Abstract-The spectral radiance measured by an airborne imaging spectrometer for a material on the Earth's surface depends strongly on the illumination incident of the material and the atmospheric conditions. This dependence has limited the success of material-identification algorithms that rely on hyperspectral image data without associated ground-truth information. In this paper, we use a comprehensive physical model to show that the set of observed 0.4-2.5 m spectral-radiance vectors for a material lies in a… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
99
0
2

Year Published

2000
2000
2023
2023

Publication Types

Select...
5
2
2

Relationship

1
8

Authors

Journals

citations
Cited by 212 publications
(101 citation statements)
references
References 38 publications
0
99
0
2
Order By: Relevance
“…We compare the predicted performance of two methods of implementing anomaly detection algorithms. For each possible target signature of interest, one might develop a subspace that encapsulates the uncertainty as to illumination and atmospheric transmission [10] and utilize a bank of subspace detectors. Alternatively, one might develop a single subspace that encapsulates all uncertainty as to the target model.…”
Section: Anomaly Detection Algorithms and The Generalized Likelihood mentioning
confidence: 99%
See 1 more Smart Citation
“…We compare the predicted performance of two methods of implementing anomaly detection algorithms. For each possible target signature of interest, one might develop a subspace that encapsulates the uncertainty as to illumination and atmospheric transmission [10] and utilize a bank of subspace detectors. Alternatively, one might develop a single subspace that encapsulates all uncertainty as to the target model.…”
Section: Anomaly Detection Algorithms and The Generalized Likelihood mentioning
confidence: 99%
“…Furthermore, if the parameters are known within a range of values, then subspace target models may be developed such that for a large set of conditions the target in radiance at the output of the sensor is well represented by the sub-space, i.e., the angle between the target and the sub-space is small [10]. Algorithms have been developed to detect targets contained within a subspace [10]- [12]. If the target subspaces are designed to be invariant to likely variation in significant parameters, then atmospheric compensation is not required for target detection purposes.…”
mentioning
confidence: 99%
“…Hyperspectral observations are described by a generative model. This model takes into account the degradation mechanisms normally found in hyperspectral applications, namely signature variability [38]- [40], abundance constraints, topography modulation, and system noise. The computation of mutual information is based on fitting mixtures of Gaussians (MOG) to data.…”
Section: Introductionmentioning
confidence: 99%
“…Spectral measurements from human tissue, for example, have been used for many years for characterization and monitoring applications in biomedicine. In remote sensing, researchers have shown that hyperspectral data are effective for material identification in scenes where other sensing modalities are ineffective [1]. The introduction of hyperspectral cameras has led to the development of techniques that combine spectral and spatial information.…”
Section: Introductionmentioning
confidence: 99%